2021
DOI: 10.3390/ijms222111547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Therapeutic Targets in Histological Subtypes of Bladder Cancer

Abstract: Histologically, bladder cancer is a heterogeneous group comprising urothelial carcinoma (UC), squamous cell carcinoma, adenocarcinomas (ACs), urachal carcinomas (UrCs), and small cell neuroendocrine carcinomas (SCCs). However, all bladder cancers have been treated so far uniformly, and targeted therapy options are still limited. Thus, we aimed to determine the protein expression/molecular status of commonly used cancer targets (programmed cell death 1 ligand 1 (PD-L1), mismatch repair (MMR), androgen and estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Behzatoglu et al reported the presence of HER2 overexpression in 56% of micropapillary carcinomas (MPCs) and only 36% of conventional BCs; on the other hand, HER2 positivity rates declined to 20% in the group of BCs with squamous differentiation (SD-BC), and no expression was seen in the cases of sarcomatoid carcinoma (SCs) and BC with glandular differentiation (GD-BC) [ 67 ], in keeping with the findings by Wang et al on a cohort of upper urinary tract UCs [ 68 ]. Even lower positivity rates (3–11%) of HER2 amplification/overexpression in SD-BCs were reported in two studies [ 69 , 70 ].…”
Section: Her2 In Divergent Differentiation and Histological Subtypes ...mentioning
confidence: 89%
“…Behzatoglu et al reported the presence of HER2 overexpression in 56% of micropapillary carcinomas (MPCs) and only 36% of conventional BCs; on the other hand, HER2 positivity rates declined to 20% in the group of BCs with squamous differentiation (SD-BC), and no expression was seen in the cases of sarcomatoid carcinoma (SCs) and BC with glandular differentiation (GD-BC) [ 67 ], in keeping with the findings by Wang et al on a cohort of upper urinary tract UCs [ 68 ]. Even lower positivity rates (3–11%) of HER2 amplification/overexpression in SD-BCs were reported in two studies [ 69 , 70 ].…”
Section: Her2 In Divergent Differentiation and Histological Subtypes ...mentioning
confidence: 89%
“…First, we examined the expression of Nectin-4 by immunohistochemistry in SCC, ADENO, and SARCO. As described in the literature, a partly cytoplasmic, partly membranous staining for Nectin-4 was observed in tumor cells [ 15 , 16 ]. Immunoreactivity was scored using the H-score as described.…”
Section: Resultsmentioning
confidence: 61%
“…14,[24][25][26] However, current studies detected potentially targetable molecular alterations in PBAC in 33.5% to 67% of cases. 26,27 Therefore, molecular testing for predictive biomarkers might be helpful in advanced cases.…”
Section: Primary Adenocarcinoma Of the Urinary Bladder And Potential ...mentioning
confidence: 62%